2022
DOI: 10.1111/cge.14289
|View full text |Cite
|
Sign up to set email alerts
|

Fatal congenital copper transport defect caused by a homozygous likely pathogenic variant of SLC31A1

Abstract: Known hereditary human diseases featuring impaired copper trafficking across cellular membranes involve ATP7A (Menkes disease, occipital horn disease, X-linked spinal muscular atrophy type 3) and ATP7B (Wilson disease). Herein, we report a newborn infant of consanguineous parents with a homozygous pathogenic variant in a highly conserved sequence of SLC31A1, coding for the copper influx transporter 1, CTR1. This missense variant, c.236T > C, was detected by whole exome sequenc-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Eventually copper replacement was stopped at the request of the parents. A second study reported a missense CTR1 variant (~236 T > C ) in a newborn infant presenting with severe low serum copper, respiratory distress, multifocal brain hemorrhages and seizures (Dame et al, 2023). The infant died at 1 month of age after cessation of ventilation intervention.…”
Section: Slc31a1 Mutationsmentioning
confidence: 99%
“…Eventually copper replacement was stopped at the request of the parents. A second study reported a missense CTR1 variant (~236 T > C ) in a newborn infant presenting with severe low serum copper, respiratory distress, multifocal brain hemorrhages and seizures (Dame et al, 2023). The infant died at 1 month of age after cessation of ventilation intervention.…”
Section: Slc31a1 Mutationsmentioning
confidence: 99%
“…This can disturb the transfer of copper to the Golgi lumen and may be responsible for the phenotypic variations seen in WD [ 156 ]. Recently, it has been shown that two mutations in the CTR1 gene in a homozygous state cause fatal copper deficiency, which also manifests as a low concentration of holo-Cp [ 157 , 158 ]. Hypothetically, the heterozygous state of these mutations can result in altered copper metabolism and may present a risk for PD development.…”
Section: Proofs For the Existence Of The Link Between Copper Dyshomeo...mentioning
confidence: 99%
“…[ 4 ] First, copper was oxidized to form toxic monovalent copper by FDX1 after transporting it into cells with recombinant human high affinity copper uptake protein (SLC31A1). [ 5 ] Furthermore, the inactivation of DLAT was directly bonded with monovalent copper and formed inactive oligomers. [ 6 ] As a result, the inactivation of DLAT down‐regulated FDX1 expression to inhibit the TCA cycle leading to the cessation of aerobic respiration.…”
Section: Introductionmentioning
confidence: 99%